Upaya Peningkatan Coping Stress terhadap Stres Akademik pada Mahasiswa Baru - Novita Maulidya Jalal; Muhrajan Piara; St. Hadjar Nurul Istiqamah; Wilda Ansar (LPPM IAIN Sorong, 2022)
Psychoeducation is one form of intervention that can be given to students in order to improve the quality of life of students, one of which is the ability to deal with academic stress. Psychoeducation efforts to improve stress coping on academic stress in new students are carried out with the aim that students experience increased stress coping in dealing with academic stress. The research was conducted with the Experiment One Group Pre test-Post test Design. The subjects in this study were 58 new students who were willing to take part in the research. The results showed the Wilcoxon test through IBM SPSS Statistics 21, the results obtained that the Asymp value. Sig.(2-tailed) for the pre-test and post-test of 0.000. Therefore, it can be concluded that this psychoeducation is effective in increasing efforts to cope with stress on academic stress in the new